2005
DOI: 10.1108/02651330510593287
|View full text |Cite
|
Sign up to set email alerts
|

Ethical segmentation of consumers in developing countries: a comparative analysis

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 72 publications
(105 reference statements)
8
71
0
Order By: Relevance
“…Al-Khatib, Vitell, and other investigators, in a series of studies conducted in different nations, have explored how consumers respond when they benefit at the expense of others or as a result of morally questionable or illegal activities. This work finds some differences among the nations investigated, but in studies conducted in Egypt (Al-Khatib et al, 1995), Romania (Al-Khatib et al, 2004), the U.S. , Saudia Arabia (Al-Khatib et al, 2005), Austria (Rawwas, 1996) and Japan (Erffmeyer et al, 1999) idealistic individuals tend to respond negatively to situations where consumers take advantage of a retailer's error, whereas relativists are more lenient. Al-Khatib et al (1995), for example, found that Egyptians who were more idealistic reacted more negatively to situations, where some might benefit but others are harmed, but individuals who endorsed a more relativistic ethics position found such situations to be more tolerable.…”
Section: Ethics Across Culturesmentioning
confidence: 77%
“…Al-Khatib, Vitell, and other investigators, in a series of studies conducted in different nations, have explored how consumers respond when they benefit at the expense of others or as a result of morally questionable or illegal activities. This work finds some differences among the nations investigated, but in studies conducted in Egypt (Al-Khatib et al, 1995), Romania (Al-Khatib et al, 2004), the U.S. , Saudia Arabia (Al-Khatib et al, 2005), Austria (Rawwas, 1996) and Japan (Erffmeyer et al, 1999) idealistic individuals tend to respond negatively to situations where consumers take advantage of a retailer's error, whereas relativists are more lenient. Al-Khatib et al (1995), for example, found that Egyptians who were more idealistic reacted more negatively to situations, where some might benefit but others are harmed, but individuals who endorsed a more relativistic ethics position found such situations to be more tolerable.…”
Section: Ethics Across Culturesmentioning
confidence: 77%
“…The literature indicates that ethical ideology is an important variable in the ethical decisionmaking process of consumers, influencing their judgments on the socially responsible activities of businesses and affecting their purchases (Al-Khatib et al, 2005;Panwar et al, 2014). …”
Section: Consumer Ethical Ideologiesmentioning
confidence: 99%
“…Cross-cultural studies have shown that consumers' predispositions towards, and engagement in, ACB differ across societies (Rawwas, 2001;Al-Khatib et al, 2005); moreover those differences reflect cultural, economic, religious, legal and social contexts (Al-Khatib et al, 1997;Rawwas et al, 1998;Rawwas, 2001;Fisher et al, 2003). Yet most studies exploring ACB have been conducted in the UK (Tonglet and Bamfield, 1997;Gill et al, 2002;Harris and Reynolds, 2004) and USA (Krasnovsky and Lane, 1998;Al-Rafee and Cronan, 2006;Goles et al, 2008) and therefore reflect the fact that "A long tradition in consumption studies has developed in Western, economically developed, societies by scholars whose backgrounds are rooted in the Western tradition of thought" (Jafari et al, 2012, p. 3).…”
Section: Globalization Implies That Understanding Consumers' Ethical mentioning
confidence: 99%
“…Al-Khatib et al (2005), for example, found that despite common social, cultural, religious and economic environments in Arabian Gulf countries, differences existed in relation to ethical beliefs and orientations. This supports the work of Alajmi et al (2011), who found that, contrary to Hofstede's (2005) claim of homogeneity in Arab cultures (Itim International, 2009), more differences than similarities exist between, for example, Kuwait and Egypt, in terms of power distance and uncertainty avoidance which could influence attitudes towards societal norms and ethical behaviour.…”
Section: Globalization Implies That Understanding Consumers' Ethical mentioning
confidence: 99%
See 1 more Smart Citation